An extensive review of preparation, stabilization, and application of single and hybrid nanofluids - Pritam Kumar Das (22047836) (2024)
The researchers attract nanofluids due to their improved thermal and physical properties compared to the base fluid. The colloidal mixture of nanometre-sized particles with conventional fluid is known as nanofluids. Compared with single nanofluids, hybrid nanofluids show better enhancement in thermophysical properties. Combining nanoparticles into the host fluid is called a hybrid nanofluid. The preparation of nanofluid needs more importance. However, the physiochemical properties of the nanofluid mainly depend on the stability of the nanofluid. The article aims to provide detailed information about preparing different types of single and hybrid nanofluids dispersed in various base fluids, preparation techniques, stabilization processes, applications and challenges. Different types of surfactants and characterization methods are suggested to improve the stability of the prepared solution. It was observed that all types of nanoparticles and hybrid nanoparticles could be synthesized with different base fluids with the help of the sonication process, particle-to-surfactant ratio, magnetic stirrer and many more. The two-step method is mostly preferred by the researchers compared to the single-step method to prepare the nanofluid. Application of single and hybrid nanofluids has been highlighted in different areas; few challenges have also been identified and must be checked before implementation in the industry. Other Information Published in: Journal of Thermal Analysis and Calorimetry License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10973-024-13449-1